Edukasi Kesehatan Tentang Pemanfaatan Pangan Lokal Bagi Penderita Diabetes Melitus Di Desa Tanoh Megakhe Kecamatan Badar Kabupaten Aceh Tenggara - Rohani Rohani; Sri Handayani; Arpina Fajarnita; Yusnaini Yusnaini (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Diabetes is a non-communicable disease (NCD) that is often suffered by Indonesian people. One of the causes of diabetes mellitus (DM) is poor lifestyle and consumption patterns. Based on this, a health education effort is needed regarding the use of local food for diabetes sufferers in Tanoh Megakhe Village, Badar District, Southeast Aceh Regency. The aim of this health education is to increase the knowledge of the Tanoh Megakhe Village community regarding diabetes mellitus and prevention efforts through consuming local food. Health education method with lectures, using leaflet media. The results of this health education program are able to increase public knowledge about the importance of maintaining diet and local food consumption patterns to avoid complications of diabetes mellitus. The conclusion that can be drawn is that health education through lecture and leaflet methods has proven to be effective in conveying information, increasing memory capacity, and stimulating changes in attitudes and behavior towards a healthy lifestyle.